(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Polypeptides have been obtained for use as carriers in polymer dosage forms containing macro- and microelements. It has been established that the optimal conditions for obtaining water-soluble polypeptides with an average molecular weight of 70,000-75,000 kDa with a maximum yield by hydrolysis of the silkworm cocoon (Bombyx mori) with caustic alkali solutions (NaOH, KOH) are: the concentration of the alkali solution is 0.250 N, the temperature of the system is 373K, the reaction time is 80 minutes. Research has determined that the resulting polypeptides do not have a negative impact on the health of animals, do not cause local irritant effects on the skin and mucous membranes of the eyes, and do not have a cumulative property.